2010
DOI: 10.2355/isijinternational.50.569
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Aluminum Erosion Behavior and Corrosion Resistance of AISI H13 Tool Steel by Oxidation Treatment

Abstract: In this work, H13 tool steel was prepared with different oxidation treatments to investigate the effects of oxidation temperature and soaking time. In order to improve erosion and corrosion resistance, this study tested with oxidation temperatures of 560°C, 580°C, and 600°C, and oxidation soaking times of 1 h, 2 h, and 3 h, respectively. Experimental results showed that the oxidation treatment at 600°C and for 3 h is the optimum process. The average thickness of the oxide layer was 9.2 mm. It showed that the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…25,26) Our previous study showed that the passivation probability in −0.4 −1.0 V crosses a potentially large range. 27) In this study, there was a slight change in the corrosion potential of the Ti-8Mo-xNi specimens, and the corrosion current varied through the different sintering temperatures and Ni contents after the corrosion tests. A lower corrosion current appeared at the 1175 C sintering temperature.…”
Section: Effect Of the Ni Content And Sintering Temperature On Corrosmentioning
confidence: 99%
“…25,26) Our previous study showed that the passivation probability in −0.4 −1.0 V crosses a potentially large range. 27) In this study, there was a slight change in the corrosion potential of the Ti-8Mo-xNi specimens, and the corrosion current varied through the different sintering temperatures and Ni contents after the corrosion tests. A lower corrosion current appeared at the 1175 C sintering temperature.…”
Section: Effect Of the Ni Content And Sintering Temperature On Corrosmentioning
confidence: 99%
“…Another factor is the Fe element that escapes from matrix, while combined with aluminum and silicon elements to generate the Fe x Al y Si z compound at the interface during the erosion test processes. 6) Significantly, the columnar structure of CrN-H13 specimen seems can effectively inhibit the formation of Fe x Al y Si z compound after 4 h corrosion test. However, it will gradually reduce the corrosion resistance after a longer test (5 h).…”
Section: (D)mentioning
confidence: 99%
“…6) Figure 3(a) shows the microstructure of a cross-section of O-H13 specimens where the depth of the oxynitriding layer is about 75 « 1 µm; and the EDS analysis (see Table 3) of a, b, and c are the coated Ni layer, Fe oxides, and the nitriding layer, respectively. Due to the outermost layer of gray oxynitriding film is very thin (12 µm) and hard to find it.…”
Section: (D)mentioning
confidence: 99%
See 2 more Smart Citations